Impact of functional constipation on psychosocial functioning and quality of life of children: A cross sectional study - H.A. Elkhayat; M.H. Shehata; A. Nada; S.M. Deifalla; M.S. Ammar (SpringerOpen, 2016)
Aim: Functional constipation (FC) is one of the common diseases among children. Many problems are common in children with FC. The aim of this study was to detect whether FC has a negative impact on the behavioral and emotional aspects, quality of life and intelligence of children. Methods: In this cross-sectional, case-control study, one hundred children participated; 50 children (mean age, 7.52 ± 2.74 years, range 4-12 years) with FC and 50 healthy children (mean age, 7.00 ± 1.52, range 4-12 years) recruited from the cases' sibs with age and sex matching to them. Behavior and emotional problems were assessed using the Arabic translation of the Child Behavior Checklist (CBCL) scores. In addition, the Arabic version of the Pediatric Quality of Life Inventory 4.0 (PedsQL™ 4.0) was used to evaluate the children's and parents' quality of life. Lastly, Stanford Binet Intelligence Scale was carried out. Results: Although, healthy control children were recruited from the patients' sibs, patients had higher CBCL scores than control children in all items except for the attention and the aggressive items. Also, total PedsQL™ 4.0 scores were lower in children with FC and their parents (p < 0.001). Furthermore, All participating children had between average and above average Stanford Binet Intelligence Scale scores and there was no score difference between patients and control (p = 0.26). Conclusion: Emotional and behavioral problems are common in children with FC so as quality of life which is compromised in those children and their parents suggesting incorporation of behavioral and quality of life screening into their diagnostic workup.